2009
DOI: 10.1007/s00125-009-1313-z
|View full text |Cite
|
Sign up to set email alerts
|

The vascular actions of insulin control its delivery to muscle and regulate the rate-limiting step in skeletal muscle insulin action

Abstract: Evidence suggests that insulin delivery to skeletal muscle interstitium is the rate-limiting step in insulin-stimulated muscle glucose uptake and that this process is impaired by insulin resistance. In this review we examine the basis for the hypothesis that insulin acts on the vasculature at three discrete steps to enhance its own delivery to muscle: (1) relaxation of resistance vessels to increase total blood flow; (2) relaxation of pre-capillary arterioles to increase the microvascular exchange surface perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
284
7
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(303 citation statements)
references
References 99 publications
5
284
7
4
Order By: Relevance
“…[41][42][43][44] . Endothelial dysfunction could be profoundly associated with less insulin delivery to the skeletal muscle interstitium, leading to decreased insulin-stimulated glucose uptake by the skeletal muscle [45][46][47][48][49] , which is implicated in the pathogenesis of insulin resistance. More directly, the restriction of the AGE content in standard mouse diets was found to markedly improve insulin resistance in obese db/db (++) mice 50 .…”
Section: Ages In Insulin Producing and Acting Tissuesmentioning
confidence: 99%
“…[41][42][43][44] . Endothelial dysfunction could be profoundly associated with less insulin delivery to the skeletal muscle interstitium, leading to decreased insulin-stimulated glucose uptake by the skeletal muscle [45][46][47][48][49] , which is implicated in the pathogenesis of insulin resistance. More directly, the restriction of the AGE content in standard mouse diets was found to markedly improve insulin resistance in obese db/db (++) mice 50 .…”
Section: Ages In Insulin Producing and Acting Tissuesmentioning
confidence: 99%
“…Both insulin and glucose promote NO synthesis in tissues (endothelium, beta cells, skeletal muscle, liver and brain) that participate in the maintenance of glucose homeostasis [1,2]. The reduced NO bioavailability that is often found in conditions of impaired glucose homeostasis is expected to involve most of these tissues since it is sustained by enhanced oxidative stress, a systemic process.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the transfer of insulin from blood to the interstitium of skeletal muscle is the rate-limiting step in insulin-dependent glucose uptake (32). Insulin induces NO-dependent vasodilatation in skeletal muscle (33) by activating IRS-2 through the phosphorylation of eNOS at Ser1177 in endothelial cells (34).…”
Section: Discussionmentioning
confidence: 99%